The Production of Economic Literature: An Interpretation - Lovell, Michael C. (Journal of Economic Literature, 1973)
A preliminary draft of this paper was presented at the Decemnber, 1971 meetings of the Econometric Society. This paper has benefited from the perceptive comments of a number of readers; I am particularly indebted to Ronald Bodkin, Stewart Gillmor, Zvi Griliches, Sherwin Rosen and the referees. Assistance in data compilation was provided by Peter Brubaker, Maureen Donahoe, Charles Eckert, Marshall E. Goldman, Stephen Kalos, Lawrence Kenny, Richard LeClair, and Thurman Northcross. Computations were executed on the Wesleyan University IBM 1130 computer. Research support has been provided by Wesleyan University and National Science Foundation Research Grant GS 2903.